Integrated nutrient management in maize (Zea mays) under different microclimatic regimes - GOGOI, TAPAN; DUTTA, RINJUMONI; SARMAH, A K; KURMI, K (The Indian Journal of Agricultural Sciences, 2022)
A field experiment entitled was conducted during summer season of 2020 and 2021 at the research farm of Assam Agricultural University, Jorhat, Assam with an objective to study the effect of microclimatic regime and integrated nutrient management in maize. The experiment was laid out in a split-plot design with 3 replications. Results revealed that among the different microclimatic regimes, crop sown on 15th March resulted in significantly higher values in almost all the growth characters, yield attributing characters, and yield as compared to other dates of sowing. Among the different integrated nutrient management practices, application of 75% of RDN through urea + 25% RDN through enriched compost (N4) recorded significantly higher value in respect of growth parameters, yield attributing characters and cob yield as compared to RDF, but remain at par with 75% of RDN through urea + 25% RDN through vermicompost (N2).